Islamic Economy: Buying and Selling, Syirkah, Rahn and Agreement of Agreements - Siti Nuri Nurhaidah; Hayatuddin Hayatuddin; Muhammad Ridwan Yahya; Evalinda Evalinda; Mudrikatul Arafah (Yayasan Adra Karima Hubbi, 2025)
Baground. The rapid rise of social media platforms, particularly TikTok and Instagram, has significantly transformed Islamic preaching (dakwah) in Indonesia. These platforms, known for their viral nature, provide a unique space for religious figures to engage with a broader audience, challenging traditional forms of religious authority and authenticity. However, the democratization of religious content on these platforms raises questions about the reliability and authenticity of the messages shared. Purpose. This study aims to investigate how TikTok and Instagram influence Islamic preaching, religious authority, and the authenticity of religious content in Indonesia. Method. Using a mixed-methods approach, the research combines content analysis of religious posts with surveys of 300 social media users to explore their engagement patterns, perceptions of authority, and trust in the content. Results. The findings reveal that TikTok users engage more with entertaining, short-form religious content, while Instagram users prefer longer, more scholarly posts. Additionally, non-traditional religious figures, particularly on TikTok, gain significant trust based on engagement rather than formal credentials. Conclucion. The study concludes that social media has reshaped the landscape of Islamic preaching, highlighting the need for new frameworks to assess religious authenticity and authority in the digital age.